The Removal of Heavy Metals from the Leachate of Aged Landfill: The Application of the Fenton Process and Nanosilica Absorbent: 10.32526/ennrj/19/202100051 - Taghavi, Kamran; Naghipour, Dariush; Ashrafi, Seyed Davoud; Salehi, Malihe (Environment and Natural Resources Journal, 2021)
Since leachate is typically composed of numerous constituents, its management requires special attention. After the raw leachate of Saravan in Rasht (Guilan Province, Iran) was transferred to a laboratory and its specifications were determined, it was subjected to experiments by the bench-scale method. The analyses of pH and heavy metals were performed in the main and control anaerobic reactors at time zero, before precipitation, and two hours after precipitation. After the anaerobic process was over and the optimal retention time was identified in the anaerobic reactor, the removal of heavy metals was analyzed by the Fenton process and nanosilica absorbent in leachate treatment. In the primary anaerobic reactor, the highest and lowest removal rates were 59 and 39% for Ni and Cu, respectively. In the Fenton process with optimal H2O2/Fe+2 ratio, Cu and Hg showed the lowest and highest removal rates of 22.4 and 54.54%, respectively. At the optimal rate of nanosilica absorbent and the retention time of 15 min, As was removed maximally with an efficiency of 38% and Cu was removed minimally. The results revealed that the integration of the anaerobic process with the Fenton process and nanosilica absorbent was very effective in removing heavy metals from the aged landfill leachate